Oxidative stress and disease: atherosclerosis - Almeida, Arthur (Henry Stewart Talks, 2026)
Reactive oxygen species, Redox signaling, Consequences of oxidative stress, Atherosclerosis, Oxidative stress and atherosclerosis, Oxidative stress targeted therapies